WHO preferred product characteristics for monoclonal antibodies for passive immunization against respiratory syncytial virus (RSV) disease in infants – Key considerations for global use. Issue 26 (9th June 2022) - Sparrow, Erin; Adetifa, Ifedayo; Chaiyakunapruk, Nathorn; Cherian, Thomas; Fell, Deshayne B.; Graham, Barney S.; Innis, Bruce; Kaslow, David C.; Karron, Ruth A.; Nair, Harish; Neuzil, Kathleen M.; Saha, Samir; et al.
Abstract: World Health Organization (WHO) preferred product characteristics describe preferences for product attributes that would help optimize value and use to address global public health needs, with a particular focus on low- and middle-income countries. Having previously published preferred product characteristics for both maternal and paediatric respiratory syncytial virus (RSV) vaccines, WHO recently published preferred product characteristics for monoclonal antibodies to prevent severe RSV disease in infants. This article summarizes the key attributes from the preferred product characteristics and discusses key considerations for future access and use of preventive RSV monoclonal antibodies.